1979
DOI: 10.3109/00016347909154904
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth retardation associated with inadequate haemodilution in otherwise uncomplicated pregnancy

Abstract: The Hb level during pregnancy was followed in 113 non-anaemic women with uncomplicated pregnancy and birth weight of the baby above the 2.5th percentile. There was an inverse correlation close to statistical significance between the birth weight of the baby and the lowest Hb level reached during pregnancy as well as the Hb level in late pregnancy (38th week). A group of seven non-anaemic women with birth weight of the baby below the 2.5th percentile had a significantly higher (p less than 0.001) Hb level in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…In addition, failure of plasma volume expansion (or high Hgb) was associated with increased risk of fetal growth restriction. [30][31][32][33] Therefore, the plasma volume expansion and consequent "anemia" are associated with fewer low-birth-weight and preterm-birth deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, failure of plasma volume expansion (or high Hgb) was associated with increased risk of fetal growth restriction. [30][31][32][33] Therefore, the plasma volume expansion and consequent "anemia" are associated with fewer low-birth-weight and preterm-birth deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal anemia has long been considered a risk factor for poor pregnancy outcome [1][2][3]. In addition, elevated hemoglobin levels have also emerged as being predictive of intrauterine growth restriction (IUGR) [1,[3][4][5][6][7][8]. An inverse association between elevated second-or third-trimester hemoglobin levels and fetal weight has been established in a general cohort of women in multiple studies [1,[3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…11 Few of the studies have also shown that increase in the Hb beyond a certain level could in fact have a negative outcome. 12 Objective of present study was to find association between maternal anaemia and neonatal complications and to find long term morbidity and mortality of babies born to anaemic mothers. …”
Section: Introductionmentioning
confidence: 99%